A Formal Requirements Model, Used in the Process of Application Code and Test Code Generation - S. N. Baranov; V. P. Kotlyarov (Моделирование и анализ информационных систем)
The considered model is used in manual development of application specifications and is based on the theory of basic protocols and respective symbolic verification tools. Means to limit the behavioral characteristics of the model still matching the source requirements are discussed. If the model is verified successfully, the executable code of the application and the respective test code are generated from the model. The technique of using the developed model is described.